Monitoring and Effect Analysis of Environmental Pollution on Oxidation Stress - Jain, Priyam; Supe, Jayant (International Journal of Scientific Research in Civil Engineering, 2020)
Oxidative stress is well known to be involved in the pathogenesis of lifestyle-related diseases, including atherosclerosis, hypertension, diabetes mellitus, ischemic diseases, and malignancies. Oxidative stress has been defined as harmful because oxygen free radicals attack biological molecules such as lipids, proteins, and DNA. However, oxidative stress also has a useful role in physiologic adaptation and in the regulation of intracellular signal transduction. Therefore, a more useful definition of oxidative stress may be “a state where oxidative forces exceed the antioxidant systems due to loss of the balance between them.” The biomarkers that can be used to assess oxidative stress in vivo have been attracting interest because the accurate measurement of such stress is necessary for investigation of its role in lifestyle diseases as well as to evaluate the efficacy of treatment. Many markers of oxidative stress have been proposed, including lipid hydroperoxides, 4-hydroxynonenal, isoprostan, 8-hydroxyguanine, and ubiquinol- 10. To prevent the development of lifestyle diseases, advice on how to lead a healthy life should be given to individuals based on the levels of oxidant and antioxidant activity assessed by pertinent biomarkers. Individual genetic information should also be taken into consideration.